PROBLEMATIKA PEMBELAJARAN BIPA DARING PADA MASA PANDEMI - Helmi Muzaki (STKIP PGRI SUMENEP, 2023)
The covid-19 pandemic makes BIPA learning cannot be done face-to-face as usual. Now BIPA learning is carried out online to facilitate learning and teaching activities so that they can continue during the Covid-19 pandemic as it is now. Such sudden changes often lead to obstacles in BIPA learning, such as the emergence of anxiety in BIPA students. The purpose of writing this research is to describe students' problems in online learning BIPA and find the right learning strategies. The method in this research uses a literature study. The results of this study found that several problems or problems resulted in a decrease in the learning motivation of BIPA students in online learning due to technical obstacles such as internet disturbances, learning methods that tend to be monotonous, and learning that is not done face-to-face and only stares at the laptop screen or computer screen, cell phones make them feel bored